Quality of Life of Wheelchair Rugby Players - Zelenka, Tomáš; Kudláček, Martin; Wittmannová, Julie (European Journal of Adapted Physical Activity, 2017)
Quality of life (QOL) of persons with disabilities has recently become focus of studies in various academic disciplines There is 250-500 thousands new cases of spinal cord injury annually, with majority being caused by accidents. Spinal cord injury (SCI) makes significant impact on person's lives as only one third of  persons with SCI are able to return to jobs they did prior to acquiring SCI and majority of them cannot return to the hobbies or sports. The purpose of this study was to show the effect of sport participation in wheelchair rugby on QOL of persons with spinal cord injury. Twenty male wheelchair rugby players - athletes with tetraplegia, who are engages in regular organized physical activity - wheelchair rugby training and competition (mean age = 32.50, SD = 8.46). Sixteen persons with tetraplegia (all males) who were not actively engaging in sports - not participating in an organized physical activity (mean age = 39.44, SD = 7.44). While results of wheelchair rugby players were higher in all four domains of QOL, the only significant difference was found in domain one focusing on perceived physical health.
Keywords: Spinal cord injury; Health; Wellbeing; Perception